Punishment for Perpetrators and Performers of Immoral Acts in the Perspective of Islamic Criminal Law (Fiqh Jinayah) - Aulia, Puja; Alfarizi, Muhammad Fadil; Rambe, Khairul Mufti (Universitas Islam Negeri Sumatera Utara, 2022)
Casual sex is now an